Anti-Asian Xenophobia, Hate Crime Victimization, and Fear of Victimization During the COVID-19 Pandemic - Lantz, Brendan (Journal of interpersonal violence, 2023)
While the World Health Organization advised against referring to COVID-19 using racial overtones, as the COVID-19 pandemic spread, many disparagingly called it the “Wuhan virus,” the “Chinese virus,” and other terms. In this context, the FBI warned police agencies about an expected increase in anti-Asian hate crimes during the early months of the pandemic. But, while some researchers and media outlets discussed these potential increases at length, very few studies have been able to directly assess the nature of anti-Asian hate and bias victimization during the pandemic. Following this, the current study directly examines variation in anti-Asian bias and victimization in the United States during the COVID-19 pandemic. Specifically, this research presents results from two studies using a survey of 3,163 non-Asian and 575 Asian American and Pacific Islander respondents, respectively. The first study examines the prevalence of anti-Asian xenophobia among the non-Asian sample and assesses differences in these prejudicial attitudes across respondent characteristics, while the second study examines variation in experiences with bias during the pandemic among the Asian sample. The results illustrate the ubiquity of anti-Asian sentiment, suggesting that those who indicate greater fear of the pandemic report more prejudicial attitudes, as well as important racial differences in these patterns. The results also demonstrate the extent to which the pandemic has impacted individual experiences with anti-Asian bias victimization, such that more than one-third of Asian respondents report bias victimization during the pandemic, and more than half of Asian respondents report that they know someone who has been victimized. These patterns have important implications for addressing COVID-19-related hate crime moving forward.